Non-Labeling Diagnostic Assessment from a Human Dignity Perspective: Implications for Students’ Academic and Character Development - Tutughamiarso, Maya Oktavia; Triwiyanto, Wahyudi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyse how the results of the Middle Years Information System (MidYIS) initial assessment can be interpreted and utilised pedagogically as a non-labelling assessment to support students’ academic and character development. A descriptive quantitative approach was used in this study, with a cross-sectional design, involving all 10th-grade students (n=35) at a private Christian high school in an urban Indonesian context as the sample, using a total sampling technique. Data were obtained from MidYIS Standard Age Scores (mean = 100, SD = 15) across six cognitive domains. The data analysis techniques in this study employed descriptive statistics and inferential statistical tests. The findings reveal significant cross-domain variation. Mathematics and Non-Verbal Reasoning demonstrate strong performance, with 45.7% of students in the Well Above to Far Above categories. In comparison, Perceptual Speed and Accuracy is the strongest domain (65.7% Above Average or higher). In contrast, Vocabulary shows greater dispersion, with 34.3% in the Below to Far Below categories. The Overall Ability mean (≈105.67) is slightly above the international benchmark, yet substantial intra-individual differences are evident, including cases of high mathematical ability alongside lower verbal performance. These results demonstrate that cognitive profiles are multidimensional and that a single ability label constitutes a scientific fallacy. MidYIS should therefore function as a reflective tool for differentiated learning rather than a predictive or labelling instrument, supporting educational practices grounded in assessment for learning and respect for human dignity.